Are neighbourhood social fragmentation and suicide associated in New Zealand? A national multilevel cohort study. Issue 12 (9th July 2009) - Collings, S; Ivory, V; Blakely, T; Atkinson, J
Abstract : Background: Studies of the association between neighbourhood fragmentation and suicide have yielded varied results, and none has simultaneously adjusted for neighbourhood fragmentation, neighbourhood deprivation and individual-level factors. Method: A multilevel analysis of a 3-year cohort study was carried out using probabilistic linkage of census and mortality records, and two measures of neighbourhood fragmentation. A total of 2.8 million respondents to the 1996 New Zealand census were followed up for 3 years for mortality (1101 suicide deaths in the analysis), aged from 20 to 74 years at follow-up. Results: No consistent association was observed between either measure of neighbourhood social fragmentation and suicide, after controlling for individual-level confounders and neighbourhood deprivation. There was some evidence of a U-shaped relationship between neighbourhood fragmentation and suicide, especially for the Congdon(NZ) index. There was no evidence of an association for a nine-variable index that captured family-type variables as well as the usual attachment-type variables. Neighbourhood deprivation remained as an important predictor of suicide rates. Conclusion: This paper highlights the importance of understanding both the measure and the wider national context when considering neighbourhood effects on suicide.